MASJID DALAM LINTASAN SEJARAH UMAT ISLAM - Syamsul Kurniawan (The Pontianak State Institute of Islamic Studies, 2014)
Today, the mosque began narrowing its function, not as it used to be especially in the period of the Prophet. Historically, at the time of Prophet Muhammad, the mosque was not restricted to function as a place of worship only (to pray and read the Quran), but served as the hub of all activities of Muslims. Based on what exemplified by the Prophet, in addition to being a place of ritual worship, the mosque also had other functions such as: first, as a place to study; second, a place to issue a fatwa; third, a place to try cases; fourth, a place for Prophet Muhammad to welcome guests/groups/representatives; fifth, a place for people to wed; sixth, a center for social services; seventh, a place for war practice; and eighth, a place for medical or health service. With a historical-theological approach, this study aims to straighten out any misunderstanding of Muslims at this time about the functions of mosques, or to give at least historical description of the mosque in the history of Muslims as a whole, as well as to explain what we should do to enliven the mosque.